Factors Determine of Muslim Customers’ Intention to Continue On Shariah Banks’ Services - Zaid, Sudirman; Hamid, Wahyuniati (International Journal of Psychosocial Rehabilitation, 2020)
The present study intends to explore the motivation and determination of Muslim in Indonesia to make use of the sharia banks’ services provided by the government to bring in Islamic values-oriented bank services. These Islamic values orientation stands in contrast to follow practices commonly known in the conventional banks. By applying planned behavior theory, it exploresthe effect of the religious norms on intention to continue on sharia banks’ services among Muslim customers. It also intends to find out whether perceived welfare capability and familiarity have effect on the intention, and their moderating role on the effect of religious norms on the intention. The results would prove that the religion norms alone does not suffice to assure continuance intention on sharia bank services The research focuses on Makassar society that is well-known of their piety in their Islamic belief, the Consumers in sharia banks serve as respondents by means of convenience sampling.